(untitled) (Bangladesh Journal of Botany, 2018)
The effect of essential oils and nano-malate in extending the vase-life of Eustoma grandiflorum Mariachii. cv. Blue flower was investigated. The treatment with 3 mM nano-malate increased flower longevity as compared to control. Nano-malate treatment increased chlorophyll, proline and carbohydrate content and membrane stability, while descreasing ACO (ACC-oxidase activity) and MDA (malondialdehyde) content and delay of senescence and peroxidation of lipids. Thyme oil was slightly effective significantly. The application of nano-malate as preservative solutions for E. grandiflorum flowers maintained the vase life of flowers for a longer period.